Health effects of housing improvement: systematic review of intervention studies. Issue 7306 (28th July 2001) - Thomson, Hilary; Petticrew, Mark; Morrison, David
Abstract: Objective: To review the evidence on the effects of interventions to improve housing on health. Design: Systematic review of experimental and non-experimental housing intervention studies that measured quantitative health outcomes. Data sources: Studies dating from 1887, in any language or format, identified from clinical, social science, and grey literature databases, personal collections, expert consultation, and reference lists. Main outcome measures: Socioeconomic change and health, illness, and social measures. Results: 18 completed primary intervention studies were identified. 11 studies were prospective, of which six had control groups. Three of the seven retrospective studies used a control group. The interventions included rehousing, refurbishment, and energy efficiency measures. Many studies showed health gains after the intervention, but the small study populations and lack of controlling for confounders limit the generalisability of these findings. Conclusions: The lack of evidence linking housing and health may be attributable to pragmatic difficulties with housing studies as well as the political climate in the United Kingdom. A holistic approach is needed that recognises the multifactorial and complex nature of poor housing and deprivation. Large scale studies that investigate the wider social context of housing interventions are required.